REVIEW PAPERThe role of mastocytosis in anaphylaxis - Marciniak, Joanna; Jutel, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
The elevated basal serum tryptase, which is accompanied in 7-8% of cases of mastocytosis has been shown the important risk factor of anaphylactic reactions in patients with hymenoptera venom hypersensitivity. Mastocytosis is the haematological disorder of mast cell proliferation in tissues. They accumulate usually in the skin, bone marrow, spleen and liver. The clinical manifestation of the disease results from the actions of mediators i.e. histamine and tryptase released during mast cell degranulation. Diagnosis of mastocytosis is based on the typical biopsy pictures of the skin, bone marrow as well as measurements of the levels of degranulation products (histamine, prostaglandin D 2 , heparin, tryptase). The treatment of mastocytosis is aimed at the blocking of either the mast cell degranulation or the effects of mast cell mediators in tissues. The avoidance of triggering factors is also important. Insect venom specific immunotherapy (SIT) has been shown to be well tolerated and effective in patiens with both mastocytosis and hymenoptera venom allergy. However, in such patients the concentration of allergen, which is injected during the vaccine shots should be increased. Currently, it is indicated to continue SIT lifelong. Case reports show that fatalities due to insect stings, which were well-tolerated during SIT appear after its discontinuation.